2022
DOI: 10.3389/fcvm.2022.958895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early phase 1 cardiac rehabilitation on cardiac function evaluated by impedance cardiography in patients with coronary heart disease and acute heart failure

Abstract: PurposeThe purpose of the study was to access the impact of phase 1 cardiac rehabilitation (CR) on cardiac function and hemodynamic changes in patients with coronary heart disease (CHD) and acute heart failure (AHF).Materials and methodsA total of 98 patients with CHD and AHF were recruited and randomized into two groups. Control group received standard pharmacotherapy and CR group received standard pharmacotherapy combined phase 1 CR. NT-proBNP and hemodynamic parameters measured by impedance cardiography (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…After analyzing the recorded indices, it is found that the mean values of the inotropic state index (ISI), ejection phase contractility index (EPCI) and left stroke work index (LSWI) are reduced in heart failure patients. Furthermore, ICG technology were used to measure hemodynamic parameters to investigate the phase I cardiac rehabilitation (CR) effect on subjects with acute heart failure (AHF) and coronary heart disease (CHD) ( Wang et al, 2022 ). Results in this work showed ameliorating in preload, systolic and diastolic functionality improvements, elevating cardiac output, and afterload relieving.…”
Section: Non-invasive Sensing Technologies Used For Heart Failure Sys...mentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the recorded indices, it is found that the mean values of the inotropic state index (ISI), ejection phase contractility index (EPCI) and left stroke work index (LSWI) are reduced in heart failure patients. Furthermore, ICG technology were used to measure hemodynamic parameters to investigate the phase I cardiac rehabilitation (CR) effect on subjects with acute heart failure (AHF) and coronary heart disease (CHD) ( Wang et al, 2022 ). Results in this work showed ameliorating in preload, systolic and diastolic functionality improvements, elevating cardiac output, and afterload relieving.…”
Section: Non-invasive Sensing Technologies Used For Heart Failure Sys...mentioning
confidence: 99%
“…The first group focuses on techniques that allow for a subtle investigation of cardiac dynamics through indirect patient contact ( Piccini and Patrick, 2007 ). The ballistocardiogram (BCG), electrocardiogram (ECG), photoplethysmography (PPG), impedance cardiography (ICG), and other crucial techniques in this field ( Aydemir et al, 2019 ; KAVAS and BOZKURT, 2022 ; Wang et al, 2022 ). These methods capture physiological signals coming from the cardiovascular system using a variety of non-invasive technologies.…”
Section: Introductionmentioning
confidence: 99%